Upaya Pemberdayaan Masyarakat dalam Meningkatkan Inklusi Pasar Modal - Geetha Wulandari Safitri; Akbarudin Akbarudin; Fransiska Juwita Waruwu; Rudi Sanjaya (International Forum of Researchers and Lecturers, 2024)
The capital market plays a significant role in spurring a country's economic growth, but capital market inclusion in Indonesia is still relatively low. This article discusses community empowerment efforts to improve capital market inclusion through financial literacy education, utilization of digital technology, and increased access to capital market products and services. It highlights the importance of early financial education, as well as the role of university students in providing training to communities, especially in remote areas. In addition, collaboration between the government, financial institutions, and financial technology (fintech) is needed to expand the reach of capital markets and increase public participation in safer and more sustainable investments.